The Intersection of a Triangular Bézier Patch and a Plane (Journal of Computational Mathematics, 1994)
In this paper, the problem of finding the intersection of a triangular Bézier patch and a plane is studied. For the degree that one frequently encounters in practice, i.e. $n=2,3$, an efficient and reliable algorithm is obtained, and computational steps are presented.